Applicability of Seismic Base Isolation in Structure - Pal, Animesh (International Journal of Scientific Research in Civil Engineering, 2018)
This paper briefly reviews the concepts, applicability and benefits of using base-isolation in structures in severe seismic zones. It is a passive means to obtain seismic response control in structure through utilizing three basic functions – horizontal flexibility, energy dissipation and rigidity against normal lateral loads. The rubber-lead bearing appears to be the best isolator performing all three functions efficiently while the base-isolation of masonry building through a planned sliding joint gets considerable attention. Conditions favor the choice of base-isolation alternative to conventional elastic or elasto-plastic designs are indicated.